Educational activity of Kyiv university professor Smogorzevsky L. A. - A. G. Lugovsky; L. K. Kuhta (History of science and technology, 2018)
The article discusses the educational activities of the Ukrainian zoologist, ornithologist L. A. Smogorzevsky. Scientific work of the scientist in 50-90-ies of the XXth century has been described. The analysis of scientific and popular publications has been performed. The role of the scientist for the ornithology promotion in modern Ukraine has been indicated.